병원자료를 이용한 사인구조 변화분석 1976-1986 - 최귀숙 (연세대학교 보건대학원, 1987)
[한글] 본 연구는 연세대학교 의과대학부속 세브란스병원에서 사망한 환자의 사인구조의 연도별생물이 차지하는 구성비율은 1976년 4.9%, 1981년 2.1%, 1986년 1.8%로 변화를 분석하여 우리나라 사람들의 사망원인의 변화를 규명하는데 간접적인 도움을 주고자 시도되었다 . 연구자료는 연세대학교 의과대학부속 세브란스병원에 입원 중 사망한 사례 중에서 1976년 306예, 1981년 434예, 그리고 1986년 380예, 총 1,120예를 대상으로 성별, 연령별 및 사인별로 분석하여 연도별 변화를 알아보았으며 전국의 사망신고 자료에 의한 사인구조와 비교하였다. 1976년 자료는 마이크로 필림화된 의무기록을 검토하여 수집하였고 1981년 및 1986년 자료는 사망장부와 의무기록을 이용하여 수집하였으며, 이를 국제질병사인분류 8차 개정판에 의거하여 분류하였다. 연구결과의 주요한 내용은 다음과 같다. 1. 1976년에서 1986년의 10년간 높은 구성비율을 차지한 사인은 신생물, 순환기계 질환, 불의의 사고·중독 및 폭력, 선천이상, 주산기 질병에 의한 것이었다. 2. 전염병 및 기생충병이 차지하는 구성비율은 1976년 13.1% 1981년 9.4%, 1986넌 6.1%로 계속 감소하는 추세에 있고 신경계 및 감각기 질환이 차지하는 구성비율도 1976년 4.9 %, 1981년 2.1%, 1986년 1.8%로 감소하고 있었다. 한편 신생물이 차지하는 구성비율은 1976%, 1981년 및 1986년에 각각 14.4%, 10.6% 및 34.7%로 급속히 증가하고 있다. 3. 국제질병사인분류 50사인분류에 의하면 1976년, 1981년 및 1986년 모두 악성 신생물에 의한 사망이 가장 많았다. 또한 불의의 사고·중독 및 폭력에 의한 사망을 제외한 국제질병사인분류 기본분류에 따르면 1976년에는 거미막하 출혈, 1986년에는 미숙아, 1986년은 위암과 선천성 심장이상으로 인한 사망이 가장 많아 연도별로 사인의 구조는 크게 변하였다. 4. 본 연구에서 나타난 사인구조는 전국의 사망신고 중 의사진단에의 한 사인구조에 가까웠다. Changes in Causes of Death in a University Hospital, 1976-1986 Choi, Kwi Sook Graduate School of Health Science and Management Yonsei University (Directed by Professor Dong Woo Lee, M.Sc.) This study was conducted to identify changes in causes of death of Koreans for the past 10 years by analyzing death records in Severance Hospital in Seoul. The total number of death studied was 1,120:306 cases for 1976, 434 for 1981 and 380 for 1986. The death records were analyzed in terms of sex, age and causes of death by calendar year. The results were also compared with national data from the death registration. Collection of records were possible from microfilm for the year of 1976 and from medical records thereafter. The International Classification of Diseases, 8th revision was used for the study. Major results are as follows; 1. Causes of death occupying major proportion during 10 years from 1976 to 1986 were malignant neoplasms, circulatory diseases, all accidents, poisonings and violence, congenital anomalies and certain causes of perinatal morbidity and mortality. 2. The proportion of infective and parasitic diseases decreased continuously from 13.1% in 1976, 9.4% in 1981 and to 6.1% in 1986. Diseases of the nervous system and sense organs has also decreased from 4.9% in 1976, 2.1% 1981 and to 1.8% 1986. On the other hand, malignant neoplasms have remarkably increased from 14.4% in 1776, 16.6% in 1981 and to 34.7% in 1986. 3. According to 50 mortality list(B list)of International Classification of Diseases, death by malignant neoplasms occupied the largest proportion in all years. Based on the standard classification except for deaths due to accidents, poisonings and violence, the pattern of causes of death varies by year: the death occupied largest proportion was subarachnoid hemorrhage in 1976, immaturity in 1981 and malignant neoplasms of stomach and congenital anomalies of heart in 1986. 4. The pattern of causes of death found in this study showed similar to those of deaths diagnosed by doctors in national death registry. [영문] This study was conducted to identify changes in causes of death of Koreans for the past 10 years by analyzing death records in Severance Hospital in Seoul. The total number of death studied was 1,120:306 cases for 1976, 434 for 1981 and 380 for 1986. The death records were analyzed in terms of sex, age and causes of death by calendar year. The results were also compared with national data from the death registration. Collection of records were possible from microfilm for the year of 1976 and from medical records thereafter. The International Classification of Diseases, 8th revision was used for the study. Major results are as follows; 1. Causes of death occupying major proportion during 10 years from 1976 to 1986 were malignant neoplasms, circulatory diseases, all accidents, poisonings and violence, congenital anomalies and certain causes of perinatal morbidity and mortality. 2. The proportion of infective and parasitic diseases decreased continuously from 13.1% in 1976, 9.4% in 1981 and to 6.1% in 1986. Diseases of the nervous system and sense organs has also decreased from 4.9% in 1976, 2.1% 1981 and to 1.8% 1986. On the other hand, malignant neoplasms have remarkably increased from 14.4% in 1776, 16.6% in 1981 and to 34.7% in 1986. 3. According to 50 mortality list(B list)of International Classification of Diseases, death by malignant neoplasms occupied the largest proportion in all years. Based on the standard classification except for deaths due to accidents, poisonings and violence, the pattern of causes of death varies by year: the death occupied largest proportion was subarachnoid hemorrhage in 1976, immaturity in 1981 and malignant neoplasms of stomach and congenital anomalies of heart in 1986. 4. The pattern of causes of death found in this study showed similar to those of deaths diagnosed by doctors in national death registry.
보건학과/석사